2018
DOI: 10.1088/1361-6528/aab7a2
|View full text |Cite
|
Sign up to set email alerts
|

High performance printed oxide field-effect transistors processed using photonic curing

Abstract: Oxide semiconductors are highly promising candidates for the most awaited, next-generation electronics, namely, printed electronics. As a fabrication route for the solution-processed/printed oxide semiconductors, photonic curing is becoming increasingly popular, as compared to the conventional thermal curing method; the former offers numerous advantages over the latter, such as low process temperatures and short exposure time and thereby, high throughput compatibility. Here, using dissimilar photonic curing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…For cooling, the substrate is kept in the box furnace over night. It should be mentioned, that other possibilities for channel formation can be utilized, such as photonic or chemical curing, to lower processing temperature 68,69 .…”
Section: Discussionmentioning
confidence: 99%
“…For cooling, the substrate is kept in the box furnace over night. It should be mentioned, that other possibilities for channel formation can be utilized, such as photonic or chemical curing, to lower processing temperature 68,69 .…”
Section: Discussionmentioning
confidence: 99%
“…In the past, it has been shown that these EGFETs perform reliably over a wide temperature range. [45][46][47] Indeed, EGFETs processed at room temperatures show lower field-effect mobility values compared to EGFETs with thermally annealed indium oxide channel. [16,[41][42][43] To achieve high performance EGFETs, the indium oxide films need to be annealed at temperatures around 400 °C.…”
Section: Electrolyte-gated Field-effect Transistors Based On Indium Omentioning
confidence: 99%
“…The nanoparticle method uses low‐temperature processing techniques; however, the method is limited by low reliability and nonuniform dispersion over large areas. The nanoparticle‐based channel TFT, in particular, shows considerably low stability due to poor channel/gate dielectric interface roughness, created by the voids between nanoparticles …”
Section: Fundamentals Of the Solution Processing Technique For Oxide mentioning
confidence: 99%
“…Research has been actively conducted to form solution‐processed oxide semiconductors at low‐temperatures using laser irradiation processes . Photoactivation with a laser enables selective processing of localized areas, delivering energy quickly and accurately.…”
Section: Low‐temperature Technology For Various Layers Of Solution‐prmentioning
confidence: 99%